Al-Ghazali’s Political Thought: Its Nature and Contemporary Relevance - ’Abd Al-Rahim, Muddathir (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Al-Ghazali’s Political Thought: Its Nature and Contemporary Relevance